2016
DOI: 10.1002/2015jb012397
|View full text |Cite
|
Sign up to set email alerts
|

Fault‐related fold styles and progressions in fold‐thrust belts: Insights from sandbox modeling

Abstract: Fault‐related folds of variable structural styles and assemblages commonly coexist in orogenic belts with competent‐incompetent interlayered sequences. Despite their commonality, the kinematic evolution of these structural styles and assemblages are often loosely constrained because multiple solutions exist in their structural progression during tectonic restoration. We use a sandbox modeling instrument with a particle image velocimetry monitor to test four designed sandbox models with multilayer competent‐inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…Regardless, extension of the fold limb is considered to have occurred during the early stages of folding by the migration of layers through the fold hinge (Mitra, ), which is consistent with the modeling results. Fourth, our focus on the 3D trishear geometry means that all of the models were based on a fault‐propagation folding style, even though previous studies have reported three end‐members (i.e., fault‐bend folding, fault‐propagation folding, and detachment folding) and note that these folding mechanisms may change over time (e.g., Apotria & Wilkerson, ; Bernard et al, ; Dixon & Liu, ; Mitra, ; Storti & Poblet, ; Watkins et al, ; Yan et al, ). Fifth, many studies have identified that the 3D geometry can vary along strike due to the presence of displacement gradients, as well as differences in the geometry of the fault plane and end‐member models (Apotria & Wilkerson, ; Wilkerson et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, extension of the fold limb is considered to have occurred during the early stages of folding by the migration of layers through the fold hinge (Mitra, ), which is consistent with the modeling results. Fourth, our focus on the 3D trishear geometry means that all of the models were based on a fault‐propagation folding style, even though previous studies have reported three end‐members (i.e., fault‐bend folding, fault‐propagation folding, and detachment folding) and note that these folding mechanisms may change over time (e.g., Apotria & Wilkerson, ; Bernard et al, ; Dixon & Liu, ; Mitra, ; Storti & Poblet, ; Watkins et al, ; Yan et al, ). Fifth, many studies have identified that the 3D geometry can vary along strike due to the presence of displacement gradients, as well as differences in the geometry of the fault plane and end‐member models (Apotria & Wilkerson, ; Wilkerson et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The Jurassic Yanshanian tectonothermal event involved a significant overprint of pre‐Jurassic structures and created a broad NE trending fold‐and‐thrust belt across South China [ Zhou et al ., ; Lin et al ., ; Yan et al ., , , ], associated with northwestward subduction of the paleo‐Pacific Plate [e.g., Zhang et al ., ; Wang et al ., ]. Subsequent Cretaceous tectonism involved crustal extension that led to widespread basin and dome generation and voluminous magmatism [ Gilder et al ., ; Zhou and Li , ; Lin et al ., ; Shu et al ., ; Kusky et al ., ; Li et al ., , , ].…”
Section: General Geologymentioning
confidence: 99%
“…1; e.g. Yan et al 2003Yan et al , 2006Yan et al , 2016Wang, Y. J. et al 2013;Qiu et al 2017). The basement in this region consists of metamorphosed Neoproterozoic shallow-marine sandy to argillaceous detrital flysch units that are intercalated with volcanic rocks Qiu et al (2015a).…”
Section: Introductionmentioning
confidence: 99%